EFFECTIVENESS OF IMPLEMENTING THE PROJECT BASED LEARNING (PJBL) LEARNING MODEL IN MATHEMATICS SUBJECTS IN ELEMENTARY SCHOOLS - Ni Putu Nadya Pratiwi; Nyoman Ayu Putri Lestari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Mataram, 2026)
In an era that continues progress, development knowledge knowledge and technology give influence big to ability source Power human. Education play role key in direct growth source Power man to direction positive. However, there are various obstacle in the learning process teaching, especially in lesson Mathematics. This subject is often viewed as a complex and challenging subject, leading to low interest and enthusiasm among students. This study aims to assess the effectiveness of implementing the Project-Based Learning method as a teaching strategy in mathematics in elementary schools. Using literature as an analytical method, this study reviews various previous publications to gather evidence regarding the effectiveness of this learning model. Through the implementation of Project-Based Learning, it is hoped that the mathematics teaching and learning process in elementary schools will become more engaging and effective.